Blooming books - Briggs, Raymond; Jones, Nicolette (Jonathan Cape in association with Puffin Books London, 2003)
Beginning with his first published illustrations in 1958, this is a diverse exploration of the artist's work. With commentaries by journalist Nicolette Jones accompanying extracts, it is divided into four sections - the early years; nursery classics; a gallery of characters; and social issues